1996
DOI: 10.1901/jaba.1996.29-573
|View full text |Cite
|
Sign up to set email alerts
|

Treating Total Liquid Refusal With Backward Chaining and Fading

Abstract: In this study, we report on a 12-year-old boy with autism, mental retardation, and a history of severe gastrointestinal problems who presented with total liquid and food refusal. Backward chaining was used to shape drinking from a cup, and a fading procedure was used to increase the quantity of water he was required to drink.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 1 publication
0
32
0
Order By: Relevance
“…Many skills taught to individuals with developmental disabilities consist of behavior chains, such as washing clothes, drinking from a cup, and following picture-activity schedules (e.g., Hagopian, Farrell, & Amari, 1996;MacDuff, Krantz, & McClannahan, 1993;McDonnell & McFarland, 1988). Prompts and reinforcement are used to teach each response in the chain in a manner that ensures that the sequence of behaviors operates as a functional unit.…”
Section: _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ __ _ _ _ _ _ _ _ _mentioning
confidence: 99%
“…Many skills taught to individuals with developmental disabilities consist of behavior chains, such as washing clothes, drinking from a cup, and following picture-activity schedules (e.g., Hagopian, Farrell, & Amari, 1996;MacDuff, Krantz, & McClannahan, 1993;McDonnell & McFarland, 1988). Prompts and reinforcement are used to teach each response in the chain in a manner that ensures that the sequence of behaviors operates as a functional unit.…”
Section: _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ __ _ _ _ _ _ _ _ _mentioning
confidence: 99%
“…The process of fading was uncomplicated, yielding a positive outcome following a relatively brief course of intervention. Another meaningful Like other studies evaluating fading procedures in the treatment of food refusal (Hagopian et al, 1996;Patel et al, 2001), we incorporated a probe assessment methodology that measured periodically consumption of the previously avoided stimulus. In the present case, each probe revealed that following exposure to fading Angie consumed a moderate amount of milk, which increased as intervention progressed, culminating in her acceptance of the full 8 ounce cup of milk once she had completed the 87.5% fading step.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that included shaping and fading methods, Hagopian, Farrell, and Amari (1996) taught a 12-year-old boy with autism and total liquid refusal to drink water from a cup. The shaping component of intervention consisted of having the boy swallow after an empty syringe was placed in his mouth and subsequently, following presentation of the syringe dipped in water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hagopian et al (1996) used backward chaining, reinforcement, and stimulus fading to treat total liquid refusal in a 12 year-old boy with ASD who was currently receiving nutrients through a central line. They task analyzed drinking from a cup into the following response chain: (a) bringing cup of water to mouth, (b) accepting water into mouth, and (c) swallowing.…”
Section: Liquid Avoidancementioning
confidence: 99%